Scanning probe microscopy characterization of immobilized enzyme molecules on a biosensor surface: Visualisation of individual molecules - Lošić Dušan; Short Ken; Gooding Justin J.; Shapter Joe G. (Journal of the Serbian Chemical Society, 2004)
Scanning probe microscopy techniques were used to study immobilized enzyme molecules of glucose oxidase (GOD) on a biosensor surface. The study was carried out in order to optimize atomic force microscopy (AFM) imaging and reveal themolecular resolution of individual GOD molecules. Chemically modified AFM tips and the light tapping mode were found to be the optimal conditions for imaging soft biomolecules such as GOD. The information obtained from the AFM images included spatial distribution and organization of the enzyme molecules on the surface, surface coverage and shape, size and orientation of individual molecules. Two typical shapes of GOD molecules were found, spherical and butterfly, which are in accordance with the shapes obtained from scanning tunnelling microscopy (STM) images. Using a model of the orientation of the GOD molecules on the surface, these shapes are assigned to the enzyme standing and lying on the surface. After AFM tip deconvolution, the size of the spherical shaped GOD molecules was found to be 12 ±2.1 nm in diameter, whereas the butterfly shapes were 16.5 ± 3.3 nm x10.2 ± 2.5 nm. Corresponding STM images showed smaller lateral dimensions of 10 _1nm_ 6 ±1nm and 6.5 ± 1 nm x5 ± 1 nm. The disagreement between these two techniques is attributed to the deformation of the GOD molecules caused by the tapping process.